Key Predictors of Proficiency in L2 Writing: Syntactic, Lexical Complexity, and Accuracy - Park, Shinjae (Studies in English Language and Education, 2025)
While many studies have examined individual aspects of complexity, accuracy, and fluency (CAF) as indicators of language performance, few have explored how syntactic complexity, lexical complexity, and accuracy function together to measure writing proficiency. This study aims to fill that gap by identifying reliable methods to measure 14 indices of syntactic complexity, 5 of lexical complexity, and 9 of accuracy. It additionally investigates how these indices contribute to holistic writing assessments. It further examines which specific indices best predict writing proficiency and determine writing quality. A total of 138 essays by Korean learners of English were analyzed using the L2 Syntactic Complexity Analyzer and Text Inspector. Multiple regression analyses were conducted to interpret the data. The results show that proficiency is best predicted by the number of coordinate phrases per clause and dependent clauses per T-unit (syntactic complexity), sophistication (lexical complexity), and article usage (accuracy). Lexical sophistication emerged as the strongest predictor of proficiency. The paper also discusses the Common European Framework of Reference for Languages (CEFR) rubrics and offers insights into selecting and categorizing writing proficiency measures. Implications for L2 writing assessment, pedagogy, and the use of automated text analysis tools are discussed, along with suggestions for future research.